1984
DOI: 10.1037/0022-3514.46.4.892
|View full text |Cite
|
Sign up to set email alerts
|

New measure of daily coping: Development and preliminary results.

Abstract: A new measure of coping with daily problems was developed for use in longitudinal studies with repeated assessments. Development began with a checklist of specific coping behaviors and cognitions taken from existing questionnaires, but adequate levels of internal consistency could not be achieved for items grouped into rationally derived coping categories. A study in which the checklist items were sorted into the categories showed that particular behaviors or cognitions could represent different types of copin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
458
7
18

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 698 publications
(504 citation statements)
references
References 16 publications
21
458
7
18
Order By: Relevance
“…No differences could be detected between the means of problemanalyzing and risky coping factors. While the first two findings are consistent with previous results , literature suggests that boys usually are more problem-oriented, using more direct actions to solve their problems (Folkman & lazarus, 1980;Stone & Neale, 1984), and they are generally perceived as being more at risk of substance abuse (Petersen, Sarigiani , & Kennedy, 1991). This is because males and females have been socialized into different gender roles , with greater emphasis being placed on autonomy and independence for boys and social relations for females (Gilligan, 1982).…”
Section: Discussionsupporting
confidence: 82%
“…No differences could be detected between the means of problemanalyzing and risky coping factors. While the first two findings are consistent with previous results , literature suggests that boys usually are more problem-oriented, using more direct actions to solve their problems (Folkman & lazarus, 1980;Stone & Neale, 1984), and they are generally perceived as being more at risk of substance abuse (Petersen, Sarigiani , & Kennedy, 1991). This is because males and females have been socialized into different gender roles , with greater emphasis being placed on autonomy and independence for boys and social relations for females (Gilligan, 1982).…”
Section: Discussionsupporting
confidence: 82%
“…These findings are in accordance with study of Stone and Neale (1990) 13 and Carver et al (1999) 14 . Analysis of emotional competence showed that adequate depth of feeling (emotional competence A) which is feeling of being confident is significantly more in men.…”
Section: Discussionsupporting
confidence: 83%
“…The first eight categories (i.e., divert attention, perspective taking, direct action, catharsis, acceptance, social support, relaxation, and spiritual support) were adopted from the study of Stone and Neale (1984). An additional "escape" category identified in our pilot studies was also appended to the list of coping categories.…”
Section: Methodsmentioning
confidence: 99%